Long‐Term Soil Structure Observatory for Monitoring Post‐Compaction Evolution of Soil Structure. Issue 4 (13th April 2017) - Keller, Thomas; Colombi, Tino; Ruiz, Siul; Manalili, Mervin Pogs; Rek, Jan; Stadelmann, Viktor; Wunderli, Hans; Breitenstein, Dani; Reiser, René; Oberholzer, Hansrudolf; Schymanski, Stanislaus; Romero-Ruiz, Alejandro; et al.
Abstract : Core Ideas: We provide long‐term data on soil structure evolution following compaction. Treatments with and without plants and with and without tillage are included. Monitoring includes soil physical and biological properties and crop measures. Compaction decreased fluid transport capability and increased mechanical impedance. The projected intensification of agriculture to meet food targets of a rapidly growing world population are likely to accentuate already acute problems of soil compaction and deteriorating soil structure in many regions of the world. The key role of soil structure for soil functions, the sensitivity of soil structure to agronomic management practices, and the lack of reliable observations and metrics for soil structure recovery rates after compaction motivated the establishment of a long‐term Soil Structure Observatory (SSO) at the Agroscope research institute in Zürich, Switzerland. The primary objective of the SSO is to provide long‐term observation data on soil structure evolution after disturbance by compaction, enabling quantification of compaction recovery rates and times. The SSO was designed to provide information on recovery of compacted soil under different post‐compaction soil management regimes, including natural recovery of bare and vegetated soil as well as recovery with and without soil tillage. This study focused on the design of the SSO and the characterization of the pre‐ and post‐compaction state of the field. We deployed a monitoring network for continuous observation of soil state variables related to hydrologic and biophysical functions (soil water content, matric potential, temperature, soil air O2 and CO2 concentrations, O2 diffusion rates, and redox states) as well as periodic sampling and in situ measurements of infiltration, mechanical impedance, soil porosity, gas and water transport properties, crop yields, earthworm populations, and plot‐scale geophysical measurements. Besides enabling quantification of recovery rates of compacted soil, we expect that data provided by the SSO will help improve our general understanding of soil structure dynamics.